Talent development in elite junior tennis: Perceptions of players, parents, and coaches - Wolfenden, L. E.; Holt, N. L. (Journal of Applied Sport Psychology, 2005)
This study examined players,' parents,' and coaches' perceptions of talent development in elite junior tennis. Nine participants (three athletes aged 13-15 yrs, four parents, and two coaches) were engaged in semi-structured interviews, which were transcribed verbatim and subjected to an inductive-deductive analysis procedure. Results revealed six categories associated with adult influence on talent development in tennis (Emotional Support, Tangible Support, Informational Support, Sacrifices, Pressure, and Relationships with Coaches). Overall, the results highlighted that parents appeared to fulfill the most significant roles in terms of providing emotional and tangible support (with the mother being more involved than the father). Parents were perceived as a source of pressure when they became over-involved in competitive settings. The role of the coach was focused on providing technical advice. Findings also showed that parents and players were required to make sacrifices. The main applied implication of this study is that involvement in elite junior tennis is a team effort whereby players, parents, and coaches fulfill specific roles.